ปัจจัยที่ส่งผลต่อประสิทธิภาพในการปฏิบัติงานของบุคลากรสำนักอำนวยการ สำนักงานอัยการจังหวัด สังกัดสำนักงานอัยการภาค 7 - Nooroopngam, Dowrung; Aticomsuwan, Supharuk; Niamhom, Wannee (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The objectives of this research were to 1) examine the level of effectiveness of personnel performance in the Prosecution Office, the Provincial Public Prosecution Office under the Office of Public Prosecution Region 7; 2) examine the level of factors affecting the effectiveness of personnel performance in the Prosecution Office; and 3) examine factors affecting the effectiveness of personnel performance in the Prosecution Office. The study population consisted of 152 people. The research instrument was a set of questionnaires. The analytical statistics were frequency, percentage, mean, standard deviation, Pearson's product-moment correlation coefficient analysis, and Stepwise multiple linear regression analysis. The reliability was calculated through Crobach's Alpha Coefficient method. The results revealed that: 1. Most of the participants were females between the ages of 41 and 50 years old. They held a bachelor's degree, were civil servants, and had work experience of more than 5 - 10 years. These participants rated the overall level of factors affecting the effectiveness of personnel performance at a high level ( = 3.73, S.D = 0.68). When examining each aspect, colleague relationships reached the highest mean level ( = 3.99, S.D = 0.63), whereas the training and development aspect had the lowest mean level ( = 3.33, S.D = 0.83). 2. The effectiveness of personnel performance was overall at a high level ( = 3.70, S.D = 0.64). When examining each aspect, the performance skills attained the highest mean level ( = 3.93, S.D = 0.55), whereas English language skills were rated at the lowest mean level ( = 2.82, S.D = 0.70). 3. The factors affecting the effectiveness of personnel performance were at the 0.01 level of significance, consisting of three aspects: colleague relationship, job security, and working environment.